Gene Polymorphisms and Susceptibility to Functional Dyspepsia: A Systematic Review and Meta-Analysis - Lijun Du; John J. Kim; Binrui Chen; Yawen Zhang; Hui Ren (Gastroenterology Research and Practice)
Functional dyspepsia (FD) is a common chronic gastrointestinal disorder with a complex, undefined mechanism. Clustering of patients with FD in families highlights the role of genetic factors in the pathogenesis of FD. We performed a systematic review and meta-analysis to clarify the associations between specific gene polymorphisms and FD susceptibility. PubMed, EMBASE, the Cochrane Library, and HuGE database were searched. An additive model was adopted to determine whether previous studied genes are associated with FD susceptibility. Carriers of minor allele in GNB3 825C>T (OR=1.15, 95% CI 0.99-1.34, P=0.07), SCL6A4 5HTTLPR (OR=0.92, 95% CI 0.75-1.12, P=0.40), and CCK-1R 779T>C (OR=0.86, 95% CI 0.72-1.03, P=0.09) genes failed to demonstrate susceptibility to FD. In a subgroup analysis, only minor allele (T) in GNB3 825C>T was associated with an increased susceptibility to the epigastric pain syndrome subtype (OR=1.34, 95% CI 1.10-1.63, P=0.003). Our meta-analysis based on available studies using an additive model failed to show that GNB3, SCL6A4, and CCK-1R polymorphisms are associated with FD susceptibility.